WidePLive: a coupled low-delay overlay construction mechanism and peer-chunk priority-based chunk scheduling for P2P live video streaming - Sina, Majid; Dehghan, Mehdi; Masoud Rahmani, Amir; Reshadi, Midia (IET communications, 2020)
In recent years, peer-to-peer (P2P) live streaming is popularised by the scalability and cost-effectiveness of P2P networks. User satisfaction in P2P live streaming systems depends on several factors, including chunk scheduling techniques and overlay construction mechanisms in these systems. P2P live streaming systems are involved with the peer and chunk selection problems to improve quality parameters of streaming, such as playback continuity, startup delay, and playback latency. In this study, WidePLive as a P2P live video streaming system is proposed. In WidePLive, the authors proposed a low-delay overlay construction mechanism and a mixed strategy based chunk scheduling scheme which are coupled together by a contribution-aware peer selection strategy as a coupling feature to improve the quality parameter. The proposed overlay construction mechanism allows new peers to have the opportunity to connect with previous peers near the server and forms a low-depth and low-delay overlay. The proposed chunk scheduling scheme uses the benefits of Rarest First and Greedy strategies to trade-off between quality parameters. The evaluation of WidePLive simulation results demonstrates an acceptable improvement in streaming performance and shows that WidePLive has lower startup delay and playback latency and higher playback continuity compared to previous works.